Grain yield and grain moisture associations with leaf, stem and root characteristics in maize - XU, Chen-chen; ZHANG, Ping; WANG, Yuan-yuan; LUO, Ning; TIAN, Bei-jing; LIU, Xi-wei; WANG, Pu; HUANG, Shou-bing (Journal of Integrative Agriculture, 2022)
Improving grain yield (GY) and reducing grain moisture (GM) are urgent demands for directly harvesting kernels with combine harvesters in maize production. GY and GM are both related to leaf, stem and root characteristics, but the relationships are not fully understood. To better understand these relationships, we conducted a field trial involving 12 maize hybrids with two sowing dates in 2017 and 10 maize hybrids with one sowing date in 2019. GY ranged from 6.5–14.6 t ha–1 in early-sown varieties and 9.3–12.7 t ha–1 in late-sown varieties in 2017, and 5.9–7.4 t ha–1 in 2019, respectively, with corresponding GM variations of 29.8–34.9%, 29.4–34.5% and 31.9–37.1% at harvest. A large maximum leaf area contributed to a high yield, a fast leaf senescence rate accelerated grain dehydration in the late growth period, and a compact root structure resulted in both of high-yield and fast-grain dehydration. A strong stem improved lodging resistance but maintained a high GM at harvest, and it is challenging to combine high GY and low GM in maize. High GY co-existed with low GM in some varieties that should have a rapid grain filling, a relatively long grain-filling duration, and a rapid grain dehydration in the late growth period. A high daily temperature in the late growth period also improved GY and reduced GM by influencing grain filling and dehydration, suggesting that adjusting the sowing date should be an alternative strategy to combine high GY and low GM in kernel harvesting.